Investment Redistributive Incentive Model (IRIM) for South Africa: a proposal for redistributive development (e-Review of Tourism Research, 2020)
This paper argues that incentives can be a useful tool to bring about change in social policy. These incentives could be linked to the exchange of know-how, share ownership, education, health, and housing. It is a conceptual paper based on secondary data. It suggests radical shifts that marry social policy and matters of corporate governance because education, health, and housing matter to people in as much as profit does to corporates. Government alone cannot solve these wicked problems of poverty, inequality, and unemployment facing contemporary society. This paper applies the Investment Redistributive Incentive Model (IRIM) in South Africa using tourism as an example. IRIM advocates linking foreign and domestic investment to redistribution of the things that matter to people in their different forms – material and non-material to alleviate poverty and inequality. The IRIM should be flexible and amenable to refinements in its application taking cognizance of local circumstances. Linking investments with social policy have the potential to shift policy and practice towards holistic societal transformation through empowering and capacitating communities by increasing their wealth while enhancing social justice and promoting inclusive, sustainable growth.